Analysis of Service Recovery Strategy in Addressing Price Inconsistency Incidents on Customer Satisfaction and Trust at Hypermart Pakuwon Mall Yogyakarta - Nila Dines Perdani; Binarin Tirto Andika (Publikasi Indonesia, 2026)
Intense competition in the retail industry requires companies not only to offer competitive prices and products, but also to ensure consistent service quality, particularly in price information management. Price inconsistency represents a form of service failure that can reduce customer satisfaction and trust if it is not handled properly. This study aims to analyze service recovery strategies in addressing price inconsistency incidents and their impact on customer satisfaction and trust at Hypermart Pakuwon Mall Jogja. This research adopts a qualitative approach using a case study method. Data were collected through in depth interviews and observations involving internal employees and customers who had experienced price inconsistency, and were analyzed using a thematic analysis approach. The findings indicate that effective service recovery strategies include prompt and professional initial responses, empathy and responsibility, price adjustments, and compensation. These strategies play a crucial role in restoring customer satisfaction and trust. This study highlights the strategic importance of service recovery in maintaining long term customer relationships in the retail context.